Product Design and Process Design of Fine Blanking Motorcycle Sprocket - Dai Longjie; Fu Zhenming (Jixie chuandong)
The motorcycle fine blanking,product design and process design small sprocket key points are introduced,including product material selection,tooth design,process parameters control and so on. Comparing to the traditional processing methods sprocket,fine blanking sprocket has the characteristics of high production efficiency,high dimensional accuracy and good bright belt.